Healthy lifestyle of a scientist as a factor for professional longevity and efficiency - M. D. Vasiliev; E. V. Makarova; A. A. Kostrov; S. A. Palevskaya; S. M. Smbatyan (Лечащий Врач, 2022)
A study of the commitment of Russian scientists to a healthy lifestyle and an assessment of behavioral and social risk factors for reducing their professional activity was fulfilled. A cross-sectional study of a single-stage section of 213 researchers from state scientific institutions in Moscow was carried out. At the age of 23 to 78 years (mean age = 45.48 ± 15.33 years), 116 women, 97 men. It was found that in the group of Russian researchers about a quarter of the respondents did not follow the principles of a healthy lifestyle well enough (25.34%). The main problem was low physical activity, identified in 79.3% of the respondents, as well as: non-compliance with the principles of rational nutrition, primarily among scientists with a teaching load; low stress management skills among doctors who combine clinical practice with science; Difficulties in interpersonal relationships in people engaged only in scientific work. In addition, a high frequency of violations and problems that can lead to a decrease in professional effectiveness has been recorded. In 9.85%, probable cognitive impairments were detected, and not associated with the age of the scientist, in 3.28% there were signs of senile asthenia, in 2.34% – senile depression. Two-thirds lived in a sub-depressive state (74.6%). Only one fifth of the respondents (19.71%, n = 42) had no cognitive impairment, no asthenic syndrome, no depression. It was concluded that risk factors for reducing professional efficiency among scientists, such as: low physical activity, poor nutrition, low stress management skills, subdepressive state, are modifiable and can be corrected, which will lead to a lesser occurrence of asthenia and cognitive impairment. It is necessary to develop and implement programs for the prevention, early diagnosis and correction of risk factors among researchers in order to maintain their effectiveness in their work and prolong their professional longevity.